Discovery of geological and archaeological things in construction site / Janidah Eman... [et al.] - Eman, Janidah; Hambali, Satira; Hussin, Abdul Aziz; Chan, Hun Beng (2008)
Discovery of geological and archaeological things at construction sites are normally unreported. There has been no recorded of findings at construction sites on the Penang Island for the past ten years (1993-2003) which is rather surprising. This research primary objective is to determine the awareness and perception of construction industry players on the Geological and Archaeological Findings. It is focus on respondent background, respondent awareness and respondent perception on issues relate to the discoveries on construction site. Questionnaires were distributed to various construction industry personnel with reference to various types of construction contracts that are applicable in Malaysia. Data analysis reveals that 75% of the respondent can define "geological and archaeological things" but only 19% understand the meaning of "antiquity". 65.9% or more of the respondent do not know the existence of National Heritage Act, Antiquities Act and Treasure Trove Act. 11.4% or less ever read National Heritage Act, Antiquities Act and Treasure Trove Act. As The World Heritage Committee during its 32nd session meeting has added Melaka and George Town as new cultural sites on the UNESCO’s World Heritage List, our society should be increased theirs awareness in the preservation of these geological and archaeological things.